Rudy - Anspaugh, David; Fried, Robert N.; Woods, Cary.; Pizzo, Angelo; Astin, Sean.; Beatty, Ned.; Dutton, Charles S.; Taylor, Lili.; Miller, Jason; Prosky, Robert, 1930-2008; Goldsmith, Jerry; Fried/Woods Films; et al. (Culver City, Calif. : Columbia TriStar Home Video, 2000)
Although people have told Rudy all his life he's not good enough, smart enough or big enough, nothing can stop his impossible dream of playing football for Notre Dame
Originally released as a motion picture in 1993
Special features include: Rudy the real story ; First down with Sean Astin ; original featurette ; isolated music score (available on one channel) ; bonus trailers ; talent files ; interactive menus ; scene selection
Music, Jerry Goldsmith ; director of photography, Oliver Wood ; editor, David Rosenbloom ; executive producer, Lee R. Mayes
Sean Astin, Ned Beatty, Charles S. Dutton, Jason Miller, Lili Taylor, Robert Prosky, Greta Lind, Jon Favreau, Scott Benjaminson, Vincent Vaughn
MPAA rating: PG
DVD, NTSC; widescreen (1.85:1) presentation
Keywords: Ruettiger, Rudy -- Drama; University of Notre Dame -- Football -- Drama; Football -- Drama; Feature films; Feature films -- United States; Football films; Video recordings for the hearing impaired; Biographical films